2004
DOI: 10.1002/jmri.20106
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of femoral orientation estimates to condylar surface and MR image plane location

Abstract: Purpose: To define the femoral anatomic region that provides the most reliable reference for measuring femoral orientation, from which patellofemoral and tibiofemoral orientation can be measured. Materials and Methods:After a three-dimensional imagebased osteo-alignment procedure, two independent estimates of distal femoral orientation, the anterior (AFA) and posterior femoral angles (PFA), were acquired. These sets were comprised of 31 axial femoral orientation estimates each (obtained across a region 10 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Thus, the Z-axis (superior) approximately aligned with the medulary axis. This alignment procedure minimized errors associated with visually aligning the humeri 39 and eliminated the dependency between the final measures and the image plane location/orientation 7; 16; 17; 42 . The anatomic planes were defined based on this alignment (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the Z-axis (superior) approximately aligned with the medulary axis. This alignment procedure minimized errors associated with visually aligning the humeri 39 and eliminated the dependency between the final measures and the image plane location/orientation 7; 16; 17; 42 . The anatomic planes were defined based on this alignment (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was based on the quantification of the complete bone surface, making the final measures insensitive to image plane orientation and location. This would not be the case if the measures were acquired in a single 2D slice 7; 16; 17; 42 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire movement cycle was used for the integration process, but all further analysis and data presentation was limited to the extension portion of the movement. The initial bone orientation was calculated using anatomically based coordinate systems (Sheehan et al, 1999;Shibanuma et al, 2004), which were identified in a single time frame only (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The initial bone orientation was calculated using anatomically based coordinate systems [24,29], which were identified in one time frame only (maximum extension). Using matrix multiplication, the attitude of all three bones throughout the movement was defined relative to these anatomic coordinate systems (Fig.…”
Section: Methodsmentioning
confidence: 99%